Hydrothermally reinforcing hydroxyaptatite and bioactive glass on carbon nanofiber scafold for bone tissue engineering - Abd El-Aziz, Asmaa M.; Serag, Eman; Kenawy, Marwa Y.; El-Maghraby, Azza; Kandil, Sherif H. (Frontiers in Bioengineering and Biotechnology, 2023)
As a bone tissue engineering scaffold, the objective of this study was to design hierarchical bioceramics based on an electrospun composite of carbon nanofibers (CNF) reinforced with hydroxyapatite (HA) and bioactive glasses (BGs) nanoparticles. The performance of the nanofiber as a scaffold for bone tissue engineering was enhanced by reinforcing it with hydroxyapatite and bioactive glass nanoparticles through a hydrothermal process. The influence of HA and BGs on the morphology and biological properties of carbon nanofibers was examined. The prepared materials were evaluated for cytotoxicity in vitro using the water-soluble tetrazolium salt assay (WST-assay) on Osteoblast-like (MG-63) cells, and oste-ocalcin (OCN), alkaline phosphatase (ALP) activity, total calcium, total protein, and tar-trate-resistant acid phosphatase (TRAcP) were measured. The WST-1, OCN, TRAcP, total calcium, total protein, and ALP activity tests demonstrated that scaffolds reinforced with HA and BGs had excellent in vitro biocompatibility (cell viability and proliferation) and were suitable for repairing damaged bone by stimulating bioactivity and biomarkers of bone cell formation.